Synthesis and Analysis of the Optical Properties of the Perovskite Material KPBBR₃ Studying the Characteristics and Potential for Application - M.O.Rahmonova; A.M.Zufarov; N.Q.Muxamadiyev (American Journal of Biodiversity, 2024)
Perovskite materials such as KPbBr₃ hold a special place in modern material science and optoelectronics due to their optical and electronic properties. The relevance of studying this material can be justified by the following factors. KPbBr₃ possesses significant optical properties such as a wide bandgap and high fluorescence. This makes it a promising material for use in devices such as LEDs, photodetectors, and solar cells. Unlike other perovskites, KPbBr₃ is composed of relatively accessible and inexpensive components. This makes it attractive for mass production and commercialization, which is especially important for the development of cost-effective optoelectronic devices. Varying the ratio of starting components in the synthesis of KPbBr₃ allows for control over its optical properties, opening up broad possibilities for optimizing the material for specific applications.